2021
DOI: 10.1016/j.bonr.2020.100734
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of osteogenesis imperfecta bone. Supramolecular assessment of cells and matrices in the context of woven and lamellar bone formation using light, polarization and ultrastructural microscopy

Abstract: Diaphyseal long bone cortical tissue from 30 patients with lethal perinatal Sillence II and progressively deforming Sillence III osteogenesis imperfecta (OI) has been studied at multiple levels of structural resolution. Interpretation in the context of woven to lamellar bone formation by mesenchymal osteoblasts (MOBLs) and surface osteoblasts (SOBLs) respectively demonstrates lamellar on woven bone synthesis as an obligate self-assembly mechanism and bone synthesis following the normal developmental pattern bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 124 publications
(107 reference statements)
0
18
0
Order By: Relevance
“…To further characterise the potential capacity for mechanotransduction, we determined the osteocyte density (N.Ot/B.Ar) of NB and EB within the hollow dome-shaped space under the CaP. For this purpose, PLM enables unequivocal discrimination between woven bone (WB) areas and lamellar bone (LB) areas [ 42 , 43 ]. Additionally, exploiting the autoluminescence from the embedding resin, correlative brightfield and epifluorescence microscopy allows distinguishing between resin-filled osteocyte lacunae and areas of ongoing mineralisation.…”
Section: Resultsmentioning
confidence: 99%
“…To further characterise the potential capacity for mechanotransduction, we determined the osteocyte density (N.Ot/B.Ar) of NB and EB within the hollow dome-shaped space under the CaP. For this purpose, PLM enables unequivocal discrimination between woven bone (WB) areas and lamellar bone (LB) areas [ 42 , 43 ]. Additionally, exploiting the autoluminescence from the embedding resin, correlative brightfield and epifluorescence microscopy allows distinguishing between resin-filled osteocyte lacunae and areas of ongoing mineralisation.…”
Section: Resultsmentioning
confidence: 99%
“…They indicated: “polarized light microscopy…showed that the interlamellar distance in both OI cases was half the normal value”. Our recent study on the histopathology of OI bone demonstrated lamellar bone in both the relatively severe progressively deforming variants as well as the benign autosomal dominant variants (Shapiro et al, 2021). We also documented the more cellular nature of both woven and lamellar OI bone compared to normal human bone; this in effect reflecting the diminished matrix synthesis in OI even though the cell components are actively attempting synthesis.…”
Section: Discussionmentioning
confidence: 97%
“…Knowledge of the histopathology of lamellar bone in OI is crucial to an ability to appropriately quantify the lamellae by PLM. The flattened elliptical shape of mature osteocytes in normal lamellar bone has been well defined, as has the fact that osteocytes in OI bone tend to a more oval shape in both animal (oim mouse model) (Carriero et al, 2014) and human (Shapiro et al, 2021) forms. The orientation of the canaliculi also clearly aids in defining the orientation of the lamellae, since canaliculi passing at right angles from the side walls of the oval/elliptical osteocyte and at right angles to the lamellae are good indicators that the lamellae have been sectioned without obliquity along their longitudinal or transverse axes (Shapiro, 1988; Kerschnitzki et al, 2011; Shapiro and Wu, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Another pathology where static and dynamic osteogenesis explains some evidence is osteogenesis imperfecta (OI), as described by Shapiro et al in 2020 [39]. The terms "static" and "dynamic" osteogenesis correspond to the definitions previously reported by Shapiro [40], i.e., with regard to the differences in osteoblast location/function in "mesenchymal osteoblasts" (MOBLs) that produce woven bone and "surface osteoblasts" (SOBLs) that produce lamellar bone.…”
Section: Experimental Evidence For So and Do Occurrencementioning
confidence: 94%
“…After the production of woven bone by MOBLs, SOBLs continued to secrete lamellar bone close to the woven scaffold. Shapiro and coworkers [39] observed in OI that "the more severe the variant of OI is, the greater the persistence of woven bone and the more immature the structural pattern; the pattern shifts to a structurally stronger lamellar arrangement once a threshold accumulation for an adequate scaffold of woven bone has been reached". The authors correlated SO and DO with the subsequent temporal phases of woven (first) and lamellar (later) bone deposition by MOBLs and SOBLs, respectively, in the production of normal/healed/pathological bone.…”
Section: Experimental Evidence For So and Do Occurrencementioning
confidence: 99%